Assessment of the Brazilian Market for Products by Carbon Dioxide Conversion - Pacheco, Kelvin A.; Reis, Alessandra C.; Bresciani, Antônio E.; Nascimento, Claudio A. O.; Alves, Rita M. B. (Frontiers in Energy Research, 2019)
Several international agreements, focused on regulating greenhouse gases emissions in the atmosphere, were created due to the growing concern about the climate change due to human action. The carbon dioxide (CO2) emissions account for more than 70% of the total greenhouse gases emissions; among the CO2 emitting sectors, electricity generation accounts for 25% of the global emissions. CO2 emissions from Brazilian power plants motivated their mapping, a method was proposed to performance a local market analysis for potential products from CO2 chemical conversion. The forecast behavior of this market for 2030 was also calculated. Among the studied products, methanol, polycarbonates, formic acid and acetaldehyde are the most promising for local manufacture. The States of São Paulo, Paraná, Amazonas, Bahia, Rio Grande do Sul and Santa Catarina are the most promising regions in terms of potential of CO2 utilization.